Production of cement based composites with three dimensional polymer lattice structures and investigation of their mechanical properties - Karabulut, Mehmet Yavuz; Yazıcıoğlu, Salih (İdris Karagöz, 2025)
In civil engineering, concrete is the most commonly used engineering material. Despite its high compressive strength, it is weak against tensile strength and shows low ductility. Reinforcement materials are used to increase the ductility of concrete. In this study, cellular lattice structures such as Gyroid and Fluorite were embedded in cement-based mortar in order to increase ductility, provide lightness and increase energy absorption capacity. In addition, the mechanical properties of cement-based composites produced with three-dimensional polymer lattice structures were investigated using control mortar (KH), fiber mortar (LH) and Gyroid mortar (GH) and Fluorite mortar (FH) produced with two different lattice configurations. The lattice structures were produced from acrylonitrile butadiene styrene (ABS) material using 3D printers by fusion deposition modelling (EBM). Samples were prepared by embedding the lattice structures in cement-based mortar. Compression, mid-loading 3-point bending test and impact tests were performed on the produced lattice-reinforced samples. According to the results obtained; The highest compressive strength value was shown by the fiber mortar (LH) sample. It was observed that the cage-reinforced cement-based mortar samples had higher energy absorption capacity. According to the results obtained from the impact strength, it was observed that the cage-structured cement-based mortar samples showed a ductile behaviour and had higher impact absorption energy values.

İnşaat mühendisliğinde beton en yaygın kullanılan mühendislik malzemesidir. Basınç dayanımının yüksek olmasına rağmen, çekme dayanımına karşı zayıftır ve düşük süneklik gösterir. Betonun sünekliğini artırmak için takviye malzemeleri kullanılır. Bu çalışmada hem sünekliğini arttırmak hem hafiflik sağlamak ve hem de enerji emme kapasitesini arttırmak için Gyroid ve Fluorite gibi hücresel kafes yapılar çimento esaslı harç içerisine gömülmüştür. Ayrıca, üç boyutlu polimer kafes yapılar ile üretilen çimento esaslı kompozitlerin mekanik özellikleri kontrol harcı (KH), lifli harç (LH) ve iki farklı kafes konfigürasyonu ile üretilen Gyroid harç (GH) ve Fluorite harç (FH) kullanılarak araştırılmıştır. Kafes yapılar eriterek biriktirme modellemesi (EBM) ile 3B yazıcılar kullanılarak akrilonitril bütadien stiren (ABS) malzemeden üretilmiştir. Kafes yapılar çimento esaslı harcın içine gömülerek numuneler hazırlanmıştır. Üretilen kafes takviyeli numuneler üzerinde basınç, orta noktadan yüklemeli 3 nokta eğilme testi ve darbe deneyleri yapılmıştır. Elde edilen sonuçlara göre; en yüksek basınç dayanım değerini lifli harç (LH) numune göstermiştir. Lifli harcın (LH) kafes takviyeli çimento esaslı harç numunelerinden daha yüksek enerji yutma kapasitesine sahip olduğu görülmüştür. Darbe dayanımından elde edilen sonuçlara göre ise kafes yapılı çimento esaslı harç numunelerin sünek bir davranış gösterdiği ve daha yüksek darbe emme enerjisi değerlerine sahip olduğu görülmüştür.
Üç boyutlu polimer kafes yapıları ile çimento esaslı kompozitlerin üretimi ve mekanik özelliklerinin incelenmesi
FDK-2022-8071
Keywords: Construction Materials; Yapı Malzemeleri